Initial psychometric testing of the coach-adapted version of the empowering and disempowering motivational climate questionnaire: A Bayesian approach. Issue 6 (18th March 2020) - Solstad, Bård Erlend; Stenling, Andreas; Ommundsen, Yngvar; Wold, Bente; Heuzé, Jean-Philippe; Sarrazin, Philippe; Castillo, Isabel; Cruz, Jaume; Hall, Howard; Papaioannou, Athanasios; Duda, Joan L.
ABSTRACT: The present study examined the psychometric properties of the coach-adapted version of the Empowering and Disempowering Motivational Climate Questionnaire (EDMCQ) using Bayesian structural equation modelling (BSEM). The sample included 780 ( M age  = 36.4; SD  = 10.8; males n = 698; females n = 54; 28 participants did not report sex) youth sport coaches representing five European countries (i.e., England, France, Greece, Norway, and Spain). The results did not support a 34-item five-factor, hierarchical, a two-factor BSEM, or a bifactor BSEM model across the participating countries. However, the results supported a reduced 19-item first-order, two-factor BSEM model that largely showed approximate metric invariance, but not approximate scalar invariance across the five countries. The pool of items constituting empowering and disempowering motivational climates should be refined to further enhance the empirical operationalisation of the coach-adapted version of the EDMCQ. Advancing the quality of translation-back-translation procedures across cultures and conducting multi-national pilot testing seems warranted as well. These recommendations may help to identify the distinctive aspects of each underlying sub-dimension of the EDMCQ, where coaches are the respondents, and pave the way for further examination of the proposed hierarchical multidimensional factor structure and the cross-cultural equivalence of the EDMCQ for this population.